COMPARATIVE RESEARCH OF JOB SATISFACTION AND JOB INVOLVEMENT BETWEEN MALE AND FEMALE IN FRESHMART BAHU MALL MANADO - Zumrotin, Tsania .; Lambey, Linda .; Tumiwa, Johan . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: To motivate employees the company must pay more attention on their job satisfaction and job involvement. A gender difference appears on satisfaction and involvement, because each gender tends to give a different perception. By knowing what each gender perception toward each variable, this research aims to see if there is significant difference between male and female employees. This research used a quantitative method. The sample of this research is male and female employees in Freshmart Bahu Mall Manado. The number of respondents is 100 employees consist of 50 male and 50 female respondents. Simple random sampling was adopted to select the respondents. The data are collected by questionnaires. The result of this research shows there are no significant differences in terms of job satisfaction and job involvement between male and female employees. The management of company may consider about the job satisfaction and job involvement and should maintaining this current condition, as well as performance, improve the service and quality of employees both for male and female employees.ÂÂKeywords: male employees, female employees, job satisfaction, job involvementÂ